INTERNALISASI PEDAGOGIK PROFETIK DALAM PEMBELAJARAN PAI SEBAGAI BASIS PENGUATAN MODERASI BERAGAMA DI SEKOLAH MENENGAH PERTAMA: (Study Kasus di SMPN 3 Subang) - Miftah Zaelani; Idris Hariri; Martalena; Dessy Prasetia Ningsih; Dinny Mardiana (STKIP Subang, 2026)
Contemporary socio-religious dynamics within formal school environments are confronted with the challenges of intolerance, radicalism, and low religious literacy among students. This study aims to analyse in depth the internalization process of prophetic pedagogy in Islamic Religious Education (PAI) as a foundation for strengthening students' religious moderation at SMP Negeri 3 Subang. Utilizing a qualitative approach with a case study design and an interpretive paradigm, data were collected through in-depth interviews, participatory observation, and documentation studies involving the principal, PAI teachers, and students. Data analysis was conducted using the Miles and Huberman interactive model, while data validity was enhanced through source and technique triangulation.The results indicate that the internalization of prophetic pedagogy is operationalized through three main pillars: humanization, liberation, and transcendence. The humanization pillar is manifested through dialogic, inclusive, and anti-discriminatory learning, thereby fostering empathy and appreciation for diversity. The liberation pillar is implemented through problem-based learning and the practice of tabayun (verification) to develop students' critical consciousness in countering hoaxes and intolerant ideologies. The transcendence pillar is realized through the habituation of a religious school culture that nurtures spiritual awareness and moral responsibility. These three pillars are integrated into the objectives, materials, methods, and evaluations of PAI learning, supported by a conducive school culture.The study concludes that prophetic pedagogy effectively contributes to shaping students' character to be moderate, tolerant, inclusive, and oriented toward humanitarian and spiritual values. These findings reinforce the position of prophetic pedagogy as a relevant Islamic educational model for strengthening religious moderation in junior high schools.